«Induçiendolas con ofrecimientos e promesas» - Javier Ruiz Astiz (Mélanges de la Casa de Velázquez)
Procuring during the Early Modern Age was one of the offences most persecuted by the civil and religious authorities for the harmful consequences that it entailed. The tendency has traditionally been to associate such conduct with elderly and disadvantaged women, but the procedural reality shows a much more complex and varied picture. This article aims to show the faces and practices of those who acted as procurers, the girls who were employed, and the persons who sought their services in Navarre under the Old Regime. At the same time, we seek to analyse the definition of the offence and its prosecution, along with the punishments meted out, through the sentences handed down by the magistrates.